2011
DOI: 10.1371/journal.pone.0021044
|View full text |Cite
|
Sign up to set email alerts
|

Region-Specific Responses of Adductor Longus Muscle to Gravitational Load-Dependent Activity in Wistar Hannover Rats

Abstract: Response of adductor longus (AL) muscle to gravitational unloading and reloading was studied. Male Wistar Hannover rats (5-wk old) were hindlimb-unloaded for 16 days with or without 16-day ambulation recovery. The electromyogram (EMG) activity in AL decreased after acute unloading, but that in the rostral region was even elevated during continuous unloading. The EMG levels in the caudal region gradually increased up to 6th day, but decreased again. Approximately 97% of fibers in the caudal region were pure typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…Because there is a possibility that decreasing muscle mass may precede the muscle strength, the disuse muscle atrophy proceeds to the muscle strength. It is important that the muscle strength is induced muscle contractions commanded from the motor area of the cerebral cortex to muscle via complex nerves after sensory receptors stimulated from EM, such as anti‐gravity posture 11. In this case, we tried to produce her active muscle contractions by sitting and standing with assistance due to EM.…”
Section: Discussionmentioning
confidence: 99%
“…Because there is a possibility that decreasing muscle mass may precede the muscle strength, the disuse muscle atrophy proceeds to the muscle strength. It is important that the muscle strength is induced muscle contractions commanded from the motor area of the cerebral cortex to muscle via complex nerves after sensory receptors stimulated from EM, such as anti‐gravity posture 11. In this case, we tried to produce her active muscle contractions by sitting and standing with assistance due to EM.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that gravitational unloading downregulates the satellite cell mitotic activity (11,(35)(36)(37)49). Furthermore, atrophy and regrowth of muscle fibers in soleus (59) and adductor longus (41) of Wistar Hannover rats were closely related to the number of satellite cells, which is also positively correlated with the distribution of myonuclei. Unloading-related decrease or loss of satellite cells was noted in the central region of soleus fibers (59) and the caudal region of adductor longus (41), in which the sarcomere length was shortened in response to passive plantarflexion of ankle joints.…”
mentioning
confidence: 86%
“…Furthermore, atrophy and regrowth of muscle fibers in soleus (59) and adductor longus (41) of Wistar Hannover rats were closely related to the number of satellite cells, which is also positively correlated with the distribution of myonuclei. Unloading-related decrease or loss of satellite cells was noted in the central region of soleus fibers (59) and the caudal region of adductor longus (41), in which the sarcomere length was shortened in response to passive plantarflexion of ankle joints. Such decrease of satellite cell distribution was increased to the control level following stretching of muscle fibers during reloading in the cage.…”
mentioning
confidence: 89%
See 2 more Smart Citations